2022
DOI: 10.1016/j.metabol.2021.155115
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeleton alterations in non-alcoholic fatty liver disease

Abstract: Background: Due to its extremely high prevalence and severity, non-alcoholic fatty liver disease (NALFD) is a serious health and economic concern worldwide.Developing effective methods of diagnosis and therapy demands a deep understanding of its molecular basis. One of the strategies in such an endeavor is the analysis of alterations in the morphology of liver cells. Such alterations, widely reported in NAFLD patients and disease models, are related to the cytoskeleton. Therefore, the fate of the cytoskeleton … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 117 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…The progression of MAFLD involves hepatocyte swelling and alterations in proteins that build the cytoskeleton. An analysis of cytoskeleton proteins may provide some information on the molecular basis of MAFLD pathogenesis and improve the NAFLD diagnosis and staging, especially in terms of the transition from benign simple steatosis to irreversible steatohepatitis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The progression of MAFLD involves hepatocyte swelling and alterations in proteins that build the cytoskeleton. An analysis of cytoskeleton proteins may provide some information on the molecular basis of MAFLD pathogenesis and improve the NAFLD diagnosis and staging, especially in terms of the transition from benign simple steatosis to irreversible steatohepatitis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The KEGG pathway analysis showed that these 354 genes were enriched in pathways including extracellular matrix (ECM)–receptor interaction, regulation of actin cytoskeleton, and focal adhesion (Figure 3 B), all of which are also implicated in NASH pathogenesis. 26 Collectively, these results, thus, suggested that various genes in the identified pathways may additively or independently contribute to NASH pathogenesis, including the fibrosis and inflammation induced by the GAN diet or adipocyte-specific PDK1 deficiency.…”
Section: Resultsmentioning
confidence: 84%
“…Recent studies have also implicated changes in the cytoskeleton in the pathophysiology of NAFLD-NASH. 26 Cytoskeletal organization responds to changes in the extracellular environment, including those in the ECM and cytokines-chemokines. 37 , 38 Adipocyte-specific PDK1 deficiency and the GAN diet may, therefore, mutually promote inflammation and fibrosis in the liver through mechanisms related to interactions between the extracellular environment and the cytoskeleton in hepatocytes and nonparenchymal cells.…”
Section: Discussionmentioning
confidence: 99%